2020
DOI: 10.11114/jets.v8i10.4995
|View full text |Cite
|
Sign up to set email alerts
|

Is There an App for That? Apps for Post-Secondary Students With Attention Hyperactivity Disorder (ADHD)

Abstract: We compiled a comprehensive list of apps related to coping with academic work by post-secondary students with attention deficit hyperactivity disorder (ADHD) by examining 23 recent sources. Most of these were based on the opinion of single individuals, including persons with ADHD and experts. To discover relatively common apps, we summed the number of sources that mentioned each app and then checked with the Apple App Store and the Google Play Store to ensure availability in the summer of 2020. In the process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The findings how that students with and without ADHD were aware of only approximately half of the apps that were recommended by experts (as listed in Fichten, et al, 2020)-although they liked most of these. It should be noted that of the 20 items that were recommended by at least two independent sources of expertise, none of the 35 students with ADHD were familiar with the following seven apps: Focus@Will, Freedom, Mindnode 5, Remember the Milk, RescueTime, Time Timer, and Voice Dream Reader.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The findings how that students with and without ADHD were aware of only approximately half of the apps that were recommended by experts (as listed in Fichten, et al, 2020)-although they liked most of these. It should be noted that of the 20 items that were recommended by at least two independent sources of expertise, none of the 35 students with ADHD were familiar with the following seven apps: Focus@Will, Freedom, Mindnode 5, Remember the Milk, RescueTime, Time Timer, and Voice Dream Reader.…”
Section: Discussionmentioning
confidence: 98%
“…Given the lacunae in the literature related to schoolwork, we carried out two studies to find out what apps and mobile technologies students with ADHD find helpful for completing their schoolwork. In Study 1, we asked whether students with and without ADHD were aware of apps that are often recommended by experts (as listed in Fichten, et al, 2020) and whether they liked any of these apps. In Study 2 we asked students with ADHD to name the apps and technologies they found helpful for completing academic work both in class and outside class.…”
Section: Purpose Of the Present Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020 we compiled a list of mobile apps that were recommended by experts for postsecondary students with ADHD to do schoolwork (Fichten et al, 2020). We based this list on 23 journal articles or items in Google and Google Scholar, published between the years 2017 and 2020.…”
Section: Apps and Mobile Devicesmentioning
confidence: 99%
“…Although computing solutions have been investigated to support children with ADHD at school or online [ 40 ], mobile technology has been less explored. Currently, there are several available mobile applications that, although not targeting children with ADHD, can support academic work for post-secondary ADHD students (e.g., Google Calendar, Everbrite) [ 41 ] or their caregivers [ 42 ]. However, the literature supporting the effectiveness of these mobile applications for students with ADHD is scant.…”
Section: Rationale For Dhi To Support Children With Adhdmentioning
confidence: 99%